DIGITAL GOVERNANCE AND CYBERSECURITY: CHALLENGES IN THE AGE OF E-GOVERNANCE - C.V., Govindraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The advent of digital governance has revolutionized public administration by enhancing transparency, efficiency, and citizen engagement. However, the rapid integration of digital technologies in governance has also amplified cybersecurity risks. This paper examines the intersection of digital governance and cybersecurity, focusing on emerging challenges faced by governments worldwide. Through a comparative analysis of India, the United States, and the European Union, this study identifies key vulnerabilities in data protection, digital infrastructure, and citizen privacy. The research emphasizes the policy gaps and proposes a framework for resilient e-governance that balances innovation with robust cybersecurity measures. Findings suggest that a multi-stakeholder approach is essential to safeguarding democratic institutions and public trust in the digital age.